Meningkatkan Hasil Belajar dengan Menggunakan Media Charta untuk Materi Sistem Pencernaan Pada Manusia Kelas VIIIA MTSN 2 Way Kanan - Akbar Setia (Universitas Muhammadiyah Kotabumi, 2020)
This research is aims to improve the results of learning students on the material of human digestive system. This research is a study the class composed of three cycle where every cycle covering the 4 stage nemely :planning, action, observation, and reflektion. The object research is the VIIIA MTsN 2 Way Kanan. The data taken in the form of the results of the competency test a well the sheets observations during the learning. From the analysis that the results of learning student increased significantly. This be seen from teh completeness studens from the results of the competency test on 30 student on VIIIA, the students completely learned as musch 50%(15 students) at the first cycle, then in the second cycle make 75%(20 students) while in the third cycle 80%(24 student).